Challenges Facing the Effective Implementation of Higher Education Policy of Digitalization in The University of Bamenda (African Journal of Law and Politics, 2025)
Like many sectors, universities have embraced the wave of digitalization as a way to improve their performance and adapt to the global technology-driven society. This paper seeks to examine the challenges facing the effective implementation of higher education policy of digitalization in the University of Bamenda. The study adopted the mixed research strategy, the target population of the study was made up of IT workers and students across the various faculties and schools that constitute the University, with a sample size comprised of 24 IT workers and 377 students, selected in line with Krecie and Morgan’s sample size determination table. The study employed the stratified random and purposive sampling techniques, and data was collected using both questionnaire and semi-structured interview guide. Findings of this study reveal that the University of Bamenda has been facing a myriad of challenges as it sought to effectively implement the policy of digitalization prescribed by the Cameroon Ministry of Higher Education. These barriers include: Lack of access to stable internet and internet-connected computers on campus, inadequate ICT infrastructure, limited users’ skills and training, unavailability of platforms for post-training management and follow-up, frequent electricity cuts, resistant to change by implementation stakeholders among other factors. These impediments are an indication that more efforts in terms of resources; financial, human and infrastructural are much required toward ensuring that the institution is effectively digitalized. The study recommended that the top management of the institution should put in place regulatory framework of digitalization that conforms to the internal realities that surround its context.